To Test or Not to Test? How a Positive Rapid Strep Test May Perplex the Diagnosis of Serum-Sickness Like Reaction - Christodoulos Chatzigrigoriadis; George Eleftherakis; Kostis Gyftopoulos; Stelios F. Assimakopoulos; Despoina Sperdouli (International Journal of Medical Students)
BACKGROUND: Serum sickness-like reaction (SSLR) represents a rare immunologic disorder. The original version is the serum sickness (SS), a type III hypersensitivity reaction caused by large protein molecules such as diphtheria antitoxin. However, SSLR is a delayed reaction of unknown etiology, triggered by small non-protein molecules. The clinical presentation of SSLR includes the classic triad of fever, rash, and arthralgia, which typically occurs 1-2 weeks after the exposure to drugs (especially β-lactams, e.g., amoxicillin and cefaclor) and infectious agents (especially viruses and Streptococcus). Some patients also present with angioedema or lymphadenopathy. The prognosis is excellent, but rare complications of liver involvement, renal involvement, coagulopathy, and pneumonitis have been reported. It is a challenging diagnosis because it mimics sepsis and other exanthematous diseases. Pharyngitis is an upper respiratory tract infection that is usually caused by viruses, but the most common bacterial cause is Streptococcus pyogenes. The Rapid Strep Test (RST) is a useful diagnostic test for detecting Streptococcus pyogenes in patients with pharyngitis and a Centor score of 3 or more guiding the administration of antibiotics.